Dual or single antiplatelet therapy after coronary surgery for acute coronary syndrome (TACSI trial): Rationale and design of an investigator-initiated, prospective, multinational, registry-based randomized clinical trial - Malm Carl Johan; Alfredsson Joakim; Erlinge David; Gudbjartsson Tomas; Gunn Jarmo; James Stefan; Møller Christian H.; Nielsen Susanne J.; Sartipy Ulrik; Tønnessen Theis; Jeppsson Anders (United States, 2025)
The TACSI trial (ClinicalTrials.gov Identifier: NCT03560310) tests the hypothesis that one-year treatment with dual antiplatelet therapy (DAPT) with acetylsalicylic acid (ASA) and ticagrelor is superior to only ASA after isolated coronary artery bypass grafting (CABG) in patients with acute coronary syndrome. The TACSI trial is an investor-initiated pragmatic, prospective, multinational, multicenter, open-label, registry-based randomized trial with 1:1 randomization to DAPT with ASA and ticagrelor or ASA only, in patients undergoing first isolated CABG, with a planned enrollment of 2200 patients at Nordic cardiac surgery centers. The primary efficacy endpoint is a composite of time to all cause death, myocardial infarction, stroke, or new coronary revascularization within 12 months after randomization. The primary safety endpoint is time to hospitalization due to major bleeding. Secondary efficacy endpoints include time to the individual components of the primary endpoint, cardiovascular death and rehospitalization due to cardiovascular causes. High-quality health-care registries are used to assess primary and secondary endpoints. The patients will be followed for 10 years. The TACSI trial will give important information useful for guiding the antiplatelet strategy in acute coronary syndrome patients treated with CABG.